(untitled) - Ferrett, Sharon K. (New York, N.Y., 2010)
This best-selling text presents new and returning college students with practical, hands-on strategies for increasing their performance inside and outside the classroom. Peak Performance helps students make the connection between their academic efforts and their job and life skills. Students learn a variety of personal productivity skills related to positive work and study habits, as well as creative problem-solving, organizational, and interpersonal skills.
Keywords: Academic achievement,Performance,Thành tích học tập,Career development,Success,Thực hiện,Phát triển nghề nghiệp